Multidimensional Assessment of COVID-19-Related Fears (MAC-RF): A Theory-Based Instrument for the Assessment of Clinically Relevant Fears During Pandemics - Schimmenti, Adriano; Starcevic, Vladan; Giardina, Alessandro; Khazaal, Yasser; Billieux, Joël (Frontiers in Psychiatry, 2020)
In this article, we present the development and psychometric properties of the Multidimensional Assessment of COVID-19-Related Fears (MAC-RF). The MAC-RF is an eight-item, self-report scale that has been developed to assess clinically relevant domains of fear during the COVID-19 pandemic. The MAC-RF is based on a comprehensive theoretical model conceptualizing fears during the pandemics as resulting from an interaction of bodily, interpersonal, cognitive and behavioral experiences. The MAC-RF was administered to a sample of 623 Italian adults from the community aged between 18 and 76 years old (M= 35.67, SD= 12.93), along with a measure of current clinical symptoms. Item Response Theory analyses demonstrated that each item of the MAC-RF provided sufficient information about the underlying construct of fear. The statistical fit of the scale was satisfactory. MAC-RF total scores correlated significantly and positively with total scores on the measure of psychopathology and with the clinical symptom domain scores. A ROC curve analysis showed that the MAC-RF total score was sufficiently able to identify cases with high levels of current psychopathology, with an area under the curve of .76. These findings suggest that the MAC-RF can be used to assess pathological fear during pandemics. The English, Italian and French versions of the MAC-RF are annexed to this article for use by clinicians and health services.